De la violencia a la convivencia en la escuela: el camino que muestran los estudios más recientes - Andrés Gómez, Soledad; Barrios, Ángela (Revista Complutense de Educación, 2009)
The study of the school conflicts, generally known as school violence, is focused social interest in the last decades in Spain and other European countries. Administrators and research groups have developed a number of studies that allow rigorous approximations to the reality of the situation in schools. The Ombusdman-UNICEF 2007 report, replication of the previous one of 2000, shows relevant data about the bullying taxes evolution in secondary at a national level. Its conclusions, as the ones from other regional studies, allow us to develop a set of intervention proposals, focused on the improvement of the school convivencia, in the way this article shows.